PENGOLAHAN LIMBAH CAIR LAUNDRY MENGGUNAKAN MEMBRAN NANOFILTRASI DENGAN KOAGULASI DAN FLOKULASI, DAN MIKROFILTRASI SEBAGAI PRETREATMENT - Okik Hendriyanto Cahyonugroho; Mahendra Clever (EnviroUS, 2022)
Laundry liquid waste is the result of waste from laundry services where the liquid waste contains substances including phosphate (P), calcium (Ca), carboxyl methyl cellulose (CMC), plant oil, clothes bleach, phosphate, surfactant, SiO32-. Total Suspended Solid (TSS), and Chemical Oxygen Demand (COD). This study was used to determine the effect of pressure variations and operating time to reduce levels of COD, TSS, Phosphate, and Detergent. The method used is a membrane micro filter and a nano filter. The best results obtained from this study were the removal of COD, TSS, Phosphate, and Detergent at a pressure of 6 bar and an operating time of 140 minutes, which had a rejection percentage of 89.15%; 81.53 ; 60,20 ; 52.15 ; with concentrations of COD, TSS, Phosphate, and Detergent respectively 64 mg/L, 65 mg/L, 6.5 mg/L, 6.8.